2022
DOI: 10.3389/fonc.2022.986516
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of inferior mesenteric vein preservation during left hemicolectomy with low ligation of the inferior mesenteric artery for distal transverse and descending colon cancers: A comparative study based on computed tomography

Abstract: PurposePresence of a long remnant sigmoid colon after left hemicolectomy with inferior mesenteric vein (IMV) ligation for distal transverse and descending colon cancers may be a risk factor for venous ischemia. This study aimed to evaluate the clinical impact of IMV preservation in patients who underwent left hemicolectomy with inferior mesenteric artery (IMA) preservation.MethodsWe included 155 patients who underwent left hemicolectomy with IMA preservation for distal transverse and descending colon cancers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Fuji et al [ 2 ] reported that congestive ischemic colitis occurred in 4 (2.1%) of the 191 patients following left-sided colectomy where the arterial branch (superior rectal artery) was preserved, and the IMV was cut near the root. Similarly, Suh et al [ 5 ] reported an incidence of 2.25% (3/133 patients). Congestive ischemic colitis is believed to be caused by venous congestion resulting from an imbalance between the arterial supply and venous return of the remnant colon after colectomy for left colon cancer[ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Fuji et al [ 2 ] reported that congestive ischemic colitis occurred in 4 (2.1%) of the 191 patients following left-sided colectomy where the arterial branch (superior rectal artery) was preserved, and the IMV was cut near the root. Similarly, Suh et al [ 5 ] reported an incidence of 2.25% (3/133 patients). Congestive ischemic colitis is believed to be caused by venous congestion resulting from an imbalance between the arterial supply and venous return of the remnant colon after colectomy for left colon cancer[ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, Suh et al [ 5 ] reported an incidence of 2.25% (3/133 patients). Congestive ischemic colitis is believed to be caused by venous congestion resulting from an imbalance between the arterial supply and venous return of the remnant colon after colectomy for left colon cancer[ 2 , 5 ]. The descending and sigmoid colons receive blood from the left colic, sigmoid, and superior rectal arteries, originating from the IMA.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Conversely, other research indicated that preserving the LCA provides better blood supply, reduces the likelihood of anastomotic leakage, and better preserves urinary and reproductive function [8][9][10]. Over the last few years, the anatomy of the inferior mesenteric vein (IMV) has also garnered increased attention, as selecting the appropriate ligation site of the IMV helps prevent postoperative congestion of the anastomosis [11][12][13]. Therefore, it is crucial to have a thorough understanding of the branching pattern of the IMV prior to surgery.…”
Section: Introductionmentioning
confidence: 99%